2022
DOI: 10.3390/antiox11050991
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Growth, Antioxidant Activity, and Immunoexpression of Proinflammatory Cytokines and Apoptotic Proteins in Broiler Chickens by Adding Dietary Spirulina platensis Phycocyanin

Abstract: This study investigated the dietary effect of Spirulina platensis phycocyanin (SPC) on growth performance (body weight (BW), body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR)) at starter, grower, and finisher stages, intestinal histomorphology, serum biochemical parameters, inflammatory and antioxidant indices, and proinflammatory cytokines (tumor necrosis factor-α and caspase-3) immune expression in broiler chickens. In total, 250 one-day-old chicks (Ross 308 broiler) were randomly allotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 61 publications
(70 reference statements)
0
18
0
Order By: Relevance
“…Numerous extracts and essential oils of particular herbs contain antioxidant characteristics that have been demonstrated to be beneficial in delaying lipid peroxidation in oils and fatty diets. These properties have attracted the attention of many researchers [ 1 , 3 , 64 , 65 ]. In the current investigation, supplementing the diet with lavender essential oil at doses of 200, 400, and 600 mg/kg linearly decreased the MDA content while linearly increasing the serum enzyme activities of TAC, CAT, and SOD in comparison with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous extracts and essential oils of particular herbs contain antioxidant characteristics that have been demonstrated to be beneficial in delaying lipid peroxidation in oils and fatty diets. These properties have attracted the attention of many researchers [ 1 , 3 , 64 , 65 ]. In the current investigation, supplementing the diet with lavender essential oil at doses of 200, 400, and 600 mg/kg linearly decreased the MDA content while linearly increasing the serum enzyme activities of TAC, CAT, and SOD in comparison with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer pressure forces the abandonment of synthetic feed additives and the mitigation of excessive breeding practices to protect the environment. Differentiating herbs that affect fatty acid characteristics and antioxidant status is a goal of several researchers [ 1 , 2 , 3 ]. The quality of poultry meat is one of the main factors affecting consumer health [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…GI =control, GII =D-gal 150 mg /kg /day, GII=spirulina 500 mg /kg /day, GIV =D-gal+Spirulina antiinflammatory homes had been located in 1998. (Abaza et al,2021, Omar et al,2022. Phycocyanin can scavenge loose radicals along with alkoxyl, hydroxyl, and peroxyl radicals.…”
Section: 85±015bmentioning
confidence: 99%
“…It was demonstrated that traditional protein sources of broiler diets could be substituted with up to 15% SP without negatively affecting the meat quality and production [ 21 , 22 , 23 ]. Additionally, it was reported that inclusion of 0.25–1.0% SP into broiler diets improved the growth efficiency, the nutrients digestibility, the antioxidant enzyme activity, the anti-inflammatory response, and the cecal microflora population [ 14 , 24 , 25 ]. In addition, Feshanghchi et al [ 26 ] found that supplementing SP at 1% to broiler diets can effectively mitigate the negative effects of aflatoxins on the broiler performance, immunological function, and blood biochemical characteristics.…”
Section: Introductionmentioning
confidence: 99%